Health promoting hospitals: a study on educational hospitals of Isfahan, Iran - Atefeh Afshari; Firoozeh Mostafavi; Mahrokh Keshvari; Leila Ahmadi-Ghahnaviye; Maryam Piruzi; Elham Moazam; Kavak Hejab; Ahmad-Ali Eslami (Tabriz University of Medical Sciences, 2016)
Background: The current situation of health promotion (HP) services in hospitals of Iran is unclear. The aim of this study was to assess the status of HP in hospitals in Isfahan, Iran. Methods: This study is a cross-sectional survey in which 9 educational hospitals selected through census sampling. HP self-assessment was used for the data collection. The assessment teams formed, and evidence examined in line with the tools. Results: The results identified five categories of HP activities in the hospitals consisted: patients,staff, environmental, community, and organizational. The mean of total score of HP was 48.8(9.8). In terms of the HP standards scores, 5 hospitals (55.5%) were at the intermediate level;3 hospitals (33.3%) were at the weak level, and 1 hospital (11.1%) was at the good level.About the standards, the highest score was "information and patient interventions" standard 79.8 (13.5), and the lowest was "continuity and cooperation" standard 36.2 (10.8). Conclusion: It seems that some of the health promoting hospitals (HPS) duties carried out by hospitals. So, to improve the quality of health services, it seems useful to encourage policymakers and health service managers to create coherent policies and guidelines in HPS.